2021
DOI: 10.12669/pjms.37.3.3700
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus Vaginal Micronized Progesterone for the treatment of threatened miscarriage

Abstract: Objectives: This study was planned with an aim to find out the effectiveness of oral versus vaginal micronized progesterone for the treatment of threatened miscarriage. Methods: This randomized controlled trial was conducted at The Department of Obstetrics and Gynaecology, Nishtar Hospital Multan, from August 2019 to January 2020. A total of 136 pregnant women, aged 18 to 45 years having vaginal bleeding were included and divided into two groups (68 women in each group). Participants in the Group-A were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This is consistent with the findings reported by Naqvi M et al 24 Strength of our study: The strength of our study is that to our knowledge there are limited studies from South Asia addressing this issue and only one study from Pakistan has evaluated association of SCH with adverse pregnancy outcomes. 18 Other local studies have addressed management 25 and outcomes of threatened miscarriage 6 without SCH or focused on the sonographic features of SCH.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings reported by Naqvi M et al 24 Strength of our study: The strength of our study is that to our knowledge there are limited studies from South Asia addressing this issue and only one study from Pakistan has evaluated association of SCH with adverse pregnancy outcomes. 18 Other local studies have addressed management 25 and outcomes of threatened miscarriage 6 without SCH or focused on the sonographic features of SCH.…”
Section: Discussionmentioning
confidence: 99%
“…20 Oral Dydrogesterone or oral micronized progesterone 400mg in two divided doses lowered the rate of miscarriage, improved fetal circulation and was found safe( non teratotenic). 21,22,23 To prevent hypertensive disorder of pregnancy and its squeal, women with threatened miscarriage need evaluation of risk factors for hypertension development and vigilant monitoring during pregnancy. History of chronic hypertension, chronic renal disease, auto-immune diseases in family, anti-phospholipid antibody syndrome, BMI 35kg/m 2 , previous history of pre-eclampia were the indicators for the start of aspirin for prophylaxis of pre-eclampsia and its sequlae.…”
Section: Discussionmentioning
confidence: 99%
“…The mean gestational age of patients in OMP group and VMP group was 31.37 ± 1.94 weeks and 33.49 ± 2.49 weeks respectively. Parveen R et al [13] randomized controlled trial found mean gestational age was 9.3+2.7 weeks.…”
Section: Comparison Of Birth Weight Of Neonates Between Groupsmentioning
confidence: 98%